Grand Orlicz spaces and global integrability of the Jacobian - Capone, C.; Fiorenza, A.; Karadzhov, G. E. (MATHEMATICA SCANDINAVICA, 2008)
We introduce and investigate the grand Orlicz spaces and the grand Lorentz-Orlicz spaces. An application to the problem of global integrability of the Jacobian of orientation preserving mappings is given.